问题
解答题
|
答案
(1)2-(
+1 4
)×1 7
,4 11
=2-
×11 28
,4 11
=2-
,1 7
=1
;6 7
(2)
÷14 9
-2 3
÷5 9
,2 3
=
×14 9
-3 2
×5 9
,3 2
=(
-14 9
)×5 9
,3 2
=1×
,3 2
=
;3 2
(3)
×72.8+723 4
÷4,4 5
=
×72.8+72.8×3 4
,1 4
=72.8×(
+3 4
),1 4
=72.8×1,
=72.8;
(4)(
+3 8
)×16+1 27
,11 27
=
×16+3 8
×16+1 27
,11 27
=6+
+16 27
,11 27
=6+(
+16 27
),11 27
=6+1,
=7;
(5)24×(
+1 4
-1 6
),1 3
=24×
+24×1 4
-24×1 6
,1 3
=6+4-8,
=2;
(6)[
-(8 15
-2 3
)]×7 15
,15 14
=[(
-8 15
+2 3
)]×7 15
,15 14
=[
+8 15
-7 15
]×2 3
,15 14
=
×1 3
,15 14
=
.5 14